Almost λr-Statistical and Strongly Almost λr-Convergence of Order β of Sequences of Fuzzy Numbers. (1st October 2015) - Işık, Mahmut; Et, Mikail
Abstract : The main purpose of this article is to introduce the concepts of almostλ r -statistical convergence and strongly almostλ r -convergence of orderβ of sequences of fuzzy numbers with respect to an Orlicz function. We give some relations between strongly almostλ r -convergence and almostλ r -statistical convergence of orderβ of sequences of fuzzy numbers.